Night and Day Are Siblings as Different in Temperament as Parent Say They Are? (article). - Saudino, Kimberly J.
Twin studies suggest that parent ratings of temperament exaggerated differences between twins. The present study examined whether such contrast effects also operate for nontwin siblings. The activity level (AL) and shyness of 95 nontwin siblings pair s (ages 3 to 8 years) were assessed via parent rating and objective measures (actigraph and observer ratings). Siblings showed no resemblance in either parent-rated AL or shyness; however, sibling resemblance for actigraph AL and observer-rated shyness was substantial. thus, parent do contrast their nontwin siblings when rating these 2 temperament dimensions. Moreover, the importance of sibling differences in temperament to the sibling relationship and differential maternal treatment varied across the different measures of AL and shyness, suggesting that parent perceptions may play a role in these associations. -- (from the author).